Analysis of Green Open Space Needs Based on Population Projections in Medan Baru Subdistrict - Tri Septiningtiyas, Dina; Darman Ferianto Saragih; Hadianti Muhdinar Pasaribu; Syiril Erwin; Meraty Ramadhini (Jurnal Inotera, 2024)
The availability of adequate green open space (RTH) is one of the efforts to maintain optimal environmental quality. The need for green open space is affected by population and area. Based on the Law No. 26 Year 2007 on Spatial Planning, it is explicitly determined that the proportion of public green open space is 20%. Sub-district Medan Baru is a sub-district located in the city center, part of which is a commercial and service area. Sub-district Medan Baru is also one of the sub-districts planned to be the city service center, which has the function of trade / business activity center, service activity center and provincial and city government activities, so the population density in the area is dense and affects the need for green space. The data used in this research are land use map, administrative map of Medan Baru sub-district and green open space coordinate data of Medan Baru sub-district. From the results of the study, it was obtained that the area of public green space in Medan Baru Sub-district is 18.78 hectares and it can be interpreted that the availability of public green space in Medan Baru Sub-district is 3.48% of the total area.